Website-Based Management and Financial Information System using Prototyping Method at GITJ Puncel Church - Yehezkiel Febri Kurniawan; Aditya Akbar Riadi; Evanita (P3M Politeknik Negeri Bengkalis, 2025)
This study aims to design and implement a web-based information system to manage ministry and financial activities at GITJ Puncel Church, focusing on improving data accuracy, reporting transparency, and operational efficiency. The system was developed using the Prototyping method with an iterative approach, while data were collected through observations, structured interviews with church administrators, and document analysis. The system was built using PHP with the Laravel framework and MySQL database, and tested using the Black Box Testing method. This research addresses gaps in previous studies that did not effectively integrate ministry management features with financial administration, nor evaluate the quantitative impact on operational efficiency. The results show that the system successfully reduced financial recording time from 3–4 hours to 30 minutes (an 87.5% efficiency improvement), decreased recording errors from 15% to 2% (an 86.7% reduction in error rate), and enhanced reporting transparency through an automatic PDF export feature. Testing confirmed that all system functionalities operated 100% according to specifications. The study's limitations include its scope being limited to a single church with 150 congregants, a three-month implementation period, and no evaluation of long-term impacts on congregation participation. Overall, this research contributes a model for integrating ministry and financial systems for small to mid-sized religious organizations, and offers a framework for evaluating the effectiveness of web-based information systems in non-profit contexts.